Identifying the influence of number of blades and distance between blades on tesla pump characteristics - Wahhab Aljibory, Mohammed; Hayawi Rahman, Mokdad (Eastern-European Journal of Enterprise Technologies, 2022)
The main principle of the Tesla pump is to increase the shear stresses as a result of the rotation of the pump blades, and thus increase the kinetic energy of the fluid to form a mass flow. The types of mechanical pumps are many and the ways of their use are wide. Over the years, scientists have contributed to developing types of pumps to get the best pump efficiency. The rotational energy can be converted into a mass flow of the fluid that can be pumped. As the Tesla pump is one of the types that gives a wide impression of fluid mechanics, where the viscosity and shear stress of the fluid will be in the movement of the fluid particles and the formation of a centrifugal force that gives an active flow of the fluid. Tesla pump is one of the primitive pumps that can be modified to study this research paper and know the number of fins used and the optimal distance between them to obtain the best mechanical efficiency of the pump. Where the Tesla pump was designed with variable fins, 3, 6 and 11 fins were taken to compare them, and the distance between the fins was reduced from 10 mm to 5 mm with a change of 2.5 mm, where the changes that occur on the pump can be observed. Where the results proved that the value of the fins increases the flow velocity of the fluid, as the best case was at the fins number 11, where the flow velocity reached 13 m/s. As for the change of distance, it is an inverse relationship as the small distance between the fins impedes the movement of the fluid flow and thus reduces the value of the flow. In the case where the number of turbine blades is 11, shear stresses reached 401 Pa. Which is the best case compared to the rest of the cases. The mechanical movement of the water was significantly increased